(untitled) (Anclajes, 2026)
It is hardly surprising that the political dimension plays a central role in El Padre Mío (1989) by Diamela Eltit and Tengo miedo torero (2001) by Pedro Lemebel, since both works engage, imaginatively or symbolically, with the Chilean dictatorship. The characters’ names intersect with this politicized framework, shaped by what we can call nominal supplementarity: a poetics of naming in which supplemental designations displace the characters’ original or “civil” names. Such nominal supplements function as mechanisms of de-subjectivation, yet they also entail simultaneous possibilities for empowerment and disempowerment, through nominal concealment and anonymity. In El Padre Mío, the loss of both identity and linguistic meaning is crystallized in the adoption of the supplement “Padre Mío”; in Tengo miedo torero, meanwhile, the supplement “la Loca del Frente” provides a form of subjective refuge and a capacity for political agency.